Local palm hearts (umbut) as potential prebiotic ingredients using in vitro colon model experimentation. - Chai, Lee Ling (2021)
Over the few past decades, rapid growth of palm trees has brought a significant impact on economic development in Malaysia. However, many parts of local palms are underutilized as scarce data available on the nutrient profiles of palm trees in Malaysia. In this study, edible core from the palm trees cultivated in Sarawak, Malaysia, notably the oil palm (Elaeis guineensis), sago palm (Metroxylon sagu) and coconut (Cocos nucifera) were investigated for their nutritive constituents and prebiotic potential. Inulin, which is a well-established prebiotic, was used as positive control. The raw and cooked palm hearts were prepared for a sequential gastrointestinal system model to study their stability in the simulated saliva, gastric and intestinal conditions. Meanwhile, the pHcontrolled batch culture system was used to delineate the fermentation properties on the colonic microbiota. Samples were obtained at 0, 6th, 12th and 24th hour for bacterial enumeration by fluorescent in situ hybridisation (FISH) and short-chain fatty acid (SCFA) analyses. Among the tested samples, sago palm hearts showed significant highest carbohydrates content (66.81 %) and significant highest potassium content (66 %). All the samples which are partially resistant to the gastrointestinal enzymatic reactions induced similar selective effects towards beneficial bacteria populations as inulin did at the end of fermentation. The highest significant decrease (p ≤ 0.05) in Clostridium histolyticum group populations was observed in the response of raw sago palm hearts at the 24th hour. In general, all the tested substrates produced significantly higher total SCFAs (p ≤ 0.05) than inulin at the 24th hour with the highest production by sago palm heart which was used as raw (286.18 mM) and cooked (284.83 mM). Overall, these findings suggested that raw local palm heart species induced a selective effect towards human gut microbiota and stimulated production of SCFA, indicating potential prebiotic ingredients.